Implementasi Metode Giving Questions And Getting Answers untuk Meningkatkan Pemahaman Siswa pada Materi Adab Bermedia Sosial di Kelas VIII MTS Darussalam Cikarang - Elda Fadlia Rahmah; Fadila Amelia; Firman Hadi Widiyanto; Ismaya Nur Asysyiddah; M. Riza Sativa Candrawan (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to improve the understanding of class VIII MTs students on the material of Social Media Etiquette through the Giving Questions and Getting Answers (GQGA) method. The research was conducted due to the low understanding of students in Islamic Religious Education subjects, especially about social media etiquette. The method used was Classroom Action Research (PTK) model Kemmis & McTaggart which consists of two cycles: planning, implementation, observation, and reflection. Data were collected through observation and multiple choice tests. As a result, students' learning completeness increased from 50% before the action, to 70% in cycle I, and 95% in cycle II. This shows that the GQGA method is effective for improving students' comprehension.